The list of unspeakable fears - Kramer, J. Kasper (Atheneum Books for Young Readers, 2022)
Essie O'Neill is afraid of everything, and things only get worse when her mother remarries and they have to move to North Brother Island where her new stepfather runs a quarantine hospital for the incurable sick. She's shocked to discover the mysterious and frightening red door from her nightmares lies right down the hall from her new bedroom. Essie knows there's something unsettling about her new home and stepfather and as she begins to investigate, she soon uncovers the horrifying truth.